(3ebGWjY GdTgjO GdWZQGFi aj GdUfYIs - (3GdWZQGFj , GdMSjf Hf Ydj Hf eMeO Hf YHO GdUeO GdCUHgGfj GdWZQGfj, eDjO GdOjf CHh ESeGYjd,J (B513 (3g` s
(3ChdgG (B:s
(3gPg ebGWjY CfTCgG HYV ef CYed acQI ai Md GdQehR ddMceGA GdbOeGA s
(3BNQgG (B:s
(3JeJ GdbUGFO GdehSheI HGdebGWjY ai GdUfYI GdcQjeI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B340s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs